Gastrointestinal pharmacology: practical tips for the esophagologist. Issue 1 (21st August 2020) - Scarpignato, Carmelo; Sloan, Joshua A.; Wang, David H.; Hunt, Richard H.
Abstract: Gastroesophageal reflux disease (GERD) is primarily a motor disorder, and its pathogenesis is multifactorial. As a consequence, treatment should be able to address the underlying pathophysiology. Proton pump inhibitors (PPIs) are the mainstay of medical therapy for GERD, but these drugs only provide the control of symptoms and lesions without curing the disease. However, continuous acid suppression with PPIs is recommended for patients with Barrett's esophagus because of their potential chemopreventive effects. In addition to the antisecretory activity, these compounds display several pharmacological properties, often overlooked in clinical practice. PPIs can indeed affect gastric motility, exert a mucosal protective effect, and an antioxidant, anti‐inflammatory, and antineoplastic activity, also protecting cancer cells from developing chemo‐ or radiotherapeutic resistance. Even in the third millennium, current pharmacologic approaches to address GERD are limited. Reflux inhibitors represent a promise unfulfilled, effective and safe prokinetics are lacking, and antidepressants, despite being effective in selected patients, give rise to adverse events in a large proportion of them. While waiting for new drug classes (like potassium‐competitive acid blockers), reassessing old drugs (namely alginate‐containing formulations), and paving the new avenue of esophageal mucosal protection are, at the present time, the only reliable alternatives to acid suppression. Abstract : Gastroesophageal reflux disease (GERD) is primarily a motor disorder, and its pathogenesis is multifactorial. As a consequence, treatment should be able to address the underlying pathophysiology. Proton pump inhibitors are the mainstay of medical therapy for GERD, but these drugs only provide the control of symptoms and lesions without curing the disease.